The Pathophysiology and Impact of Inflammation in Nonscarred Renal Interstitium: The Banff i Lesion. Issue 4 (April 2020) - Nankivell, Brian J.; P'Ng, Chow H.; Shingde, Meena; Viswanathan, Seethalakshmi; Achan, Anita; Renthawa, Jasveen; Sharma, Raghwa N.; Chapman, Jeremy R.
Abstract : Background: Interstitial inflammation (i-INT) is the driver of T-cell–mediated rejection. Its causes, pathophysiology, kinetics, and outcomes are poorly documented. Methods: The role of i-INT was evaluated in 2055 biopsies from 775 renal transplant recipients. Results: i-INT was present in 374 (18.2% prevalence) from acute and subclinical rejection (67.4%); interstitial fibrosis and tubular atrophy (14.4%); BK virus nephropathy (BKVAN) 9.9%; and acute tubular necrosis (ATN with i-INT) in 5.9% of cases. i-INT was predicted by prior T-cell–mediated rejection and BKVAN, human leukocyte antigen mismatch, cyclosporine therapy, and indication biopsy for dysfunction. It correlated with tubulitis, arteritis, and antibody markers within concurrent histology ( P < 0.001). After treatment, renal functional recovery was best with histological ATN, milder i-INT, and early posttransplant biopsy times. The initial histological improvement of inflammation depended on baseline i-INT severity. Complete resolution to Banff i0 was predicted by early biopsy time, antilymphocyte therapy, recipient age, and medication compliance (all P < 0.001). Clearance i-INT was followed by delayed resolution of tubulitis ( P < 0.001). i-INT was associated with histological ATN, renal dysfunction, and increased incident fibrosis on sequential pathology. Progressive fibrosis following related-rejection i-INT was dependent on tubulitis using multivariable analysis. In contrast, fibrogenesis after BKVAN or ATN was unrelated to inflammation. i-INT cases were followed by recurrent rejection in 35.3%, increased graft loss, and greater patient mortality. Multiple complementary outcome analyses determined the optimal lower diagnostic threshold for inflammation was Banff i1 score. Conclusions: i-INT is a heterogeneous pathological phenotype that results in adverse functional and structural outcomes, for which active and robust therapy should be considered. Abstract : Supplemental Digital Content is available in the text.